HUMAN RIGHTS FOR CONVICTED TERRORISTS WHO WOULD FACE DEATH PENALTY - Lubis, Fauziah (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2023)
This study is to observe how human rights should be considered to convicted terrorists who would face death penalty. This study involves juridical and-normative approach which focus to pass the norms within positive law. This study discovers that death penalty could be passed to terrorism crime. There is polemic among governments, legal practitioners, religious figures, and public in terms of consistency in passing death penalty. The main reason is human rights. Passing the death penalty to the convicted terrorists is regarded as violation to the human rights unless the basic rights is lawfully fulfilled by the state. Death penalty could be passed to convicted terrorists constitutionally. The lookout to the human rights in passing the death penalty to the convincted terrorists should receive greater attention to avoid psychological burden of the delayed execution after the judge’s verdict and procession to ask for pardon, amnesty, abolishment, and rehabilitation. As a result, the government and the law enforcement bodies such as acting attorneys must have an enormous authority to pass the execution immediately